Review on Chemistry and Bioactivities of Secondary Metabolites from Some Medicinal Plants and Microbes of Bangladesh (Bangladesh Pharmaceutical Journal, 2015)
Plants and microorganisms, being the major source of many drugs, have attracted scientists from ancient times. However, until recently an insignificant part of the plants and some microorganisms have scientifically been evaluated for their medicinal values. The present study was undertaken to discover new drug candidates from natural sources. Extensive chemical studies with 60 medicinal plants and several microbial strains of Bangladesh have resulted in the isolation and characterization of 150 compounds, including 50 new molecules. Terpenoids and alkaloids were the major constituents among the isolated compounds. The crude extractives and several purified molecules demonstrated statistically significant inhibition of growth of microorganisms, antioxidant, antidiabetic and HIV-inhibitory activities. Usnic acid, a lead compound isolated from the lichen, Parmelia kamtschandalis, showed potent antimicrobial activity, whereas dehydroaltenusin obtained from a Streptomyces sp. exhibited significant HIV-inhibitory effects. DOI: http://dx.doi.org/10.3329/bpj.v17i1.22307 Bangladesh Pharmaceutical Journal 17(1): 1-17, 2014